2022
DOI: 10.3390/ijms232113320
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease and Chronic Kidney Disease: Epidemiology, Pathogenesis, and Clinical and Research Implications

Abstract: Nonalcoholic fatty liver disease (NAFLD) has become the most common cause of chronic liver disease worldwide, affecting up to ~30% of adult populations. NAFLD defines a spectrum of progressive liver conditions ranging from simple steatosis to nonalcoholic steatohepatitis (NASH), cirrhosis, and hepatocellular carcinoma, which often occur in close and bidirectional associations with metabolic disorders. Chronic kidney disease (CKD) is characterized by anatomic and/or functional renal damage, ultimately resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 159 publications
0
21
0
2
Order By: Relevance
“…NAFLD and CKD are both significant global public health burden, and there is evidence that NAFLD is independently associated with a high risk of CKD despite the exclusion of other metabolic diseases, while the underlying mechanisms are not clear (26). In our study, by obtaining DEGs and important module genes by WGCNA, 45 NAFLD-related share genes were obtained, and their enrichment analysis revealed that immune, inflammatory and programmed cell death pathways were significantly enriched.…”
Section: Discussionmentioning
confidence: 82%
“…NAFLD and CKD are both significant global public health burden, and there is evidence that NAFLD is independently associated with a high risk of CKD despite the exclusion of other metabolic diseases, while the underlying mechanisms are not clear (26). In our study, by obtaining DEGs and important module genes by WGCNA, 45 NAFLD-related share genes were obtained, and their enrichment analysis revealed that immune, inflammatory and programmed cell death pathways were significantly enriched.…”
Section: Discussionmentioning
confidence: 82%
“…45,46 Finally, the hepato-renal reflex may also play a potential role in promoting the occurrence and development of MAFLD-CKD. 47 Given the close association between MAFLD and CKD, it is reasonable to hypothesize that the severity of MAFLD may exacerbate the risk of developing MAFLD-CKD. There is little evidence that patients with MAFLD with steatohepatitis or severe fibrosis have a higher risk of MAFLD-CKD than individuals without fibrosis or with isolated steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] Furthermore, subclinical portal hypertension can occur in non-cirrhotic MASLD, which can impair renal vasoregulation. 26,27 Recently, it was shown that hepatic steatosis does not predict incident CVD and related mortality when taking into account changes in cardiovascular risk factors over time, 28 suggesting that especially MASLD-related hepatic inflammation and fibrosis with resulting liver stiffness are the most important contributors to the onset and progression of CVD. [29][30][31][32][33] Of note, increased liver stiffness does not solely result from liver disease-related fibrogenesis but also from increased central venous pressure and congestive hepatopathy.…”
Section: Introductionmentioning
confidence: 99%